Information technology (IT) policy innovation to improve the quality of public services through the e-government program in Sidenreng Rappang District - Irwan, Irwan; HERMANSYAH, SAM; Uceng, Andi (IHSA Institute, 2023)
The main research problem is the relationship between the executive and the legislature in the process of formulating the issuance of Regional Regulation No. 7 of 2016 concerning the Wajo Regency APBD. Then, data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions, then the data sources used are, 1) Primary Data, primary data is a source of research data obtained directly from the original source. 2) Secondary data, secondary data is a source of research data obtained through media or intermediaries or indirectly in the form of books. The purpose of this research is to, 1) to describe and analyze the relationship between the legislature and the executive in the process of formulating the issuance of Regional Regulation No. 7 of 2016 concerning the Wajo Regency APBD, 2) to express Community Responses to the realization of the formulation of the Regional Budget Regional Regulation of the Regency of Wajo. Wajo. The result of this study is that the formulation of the issuance of the Wajo Regency APBD shows that the executive role dominates the issuance of the Wajo Regency Regional Budget Regulation and in the making of the Regency Regional Regulation. Wajo The enactment of the APBD regional regulation did not encounter obstacles that could burden the issuance of the APBD regional regulation which was carried out by the Regent or the executive. The stipulation of the APBD regional regulation occurs as a conspiracy or a clash of political and economic interests between the executive and the legislature. It can be seen that the power relationship between the executive and the legislature is driven by the executive or in this case the Regent of Wajo.